The Impact of Covid-19 Pandemic Crisis Toward Indonesian Economy - Oskar Hutagaluh; Kok Shiong Pong (INTERNATIONAL JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS (INJOSS), 2022)
A recent example where the implementation of this new normal policy has even become counterproductive is the regulation regarding the requirement to obtain an Entry Permit (SIKM) in carrying out activities in the new normal era, which was stipulated by several local governments. In practice, this regulation becomes a burden that burdens the community, because in addition to complicated management, it also involves significant costs. The winding road to getting back to work in this new normal era for inter-regional workers is also added to the rules for having to undergo polymerase chain reaction (PCR) or rapid tests issued by the Task Force for the Acceleration of Handling COVID-19. So it is not surprising that many then cancel their activities, including airlines that also cancel flights. This can have an impact on the economy for the community.